Magnetic Susceptibility of Volcanic Soil on the Surface of Mount Singgalang, Sumatra Barat: Azmi Renaldi Renaldi Alrahmadana, Hamdi Rifai, Syafriani Syafriani, Fatni Mufit, Nofi Yendri Sudiar - Azmi Renaldi Renaldi Alrahmadana Azmi Renaldi Renaldi Alrahmadana; Hamdi Rifai Hamdi Rifai; Syafriani Syafriani; Fatni Mufit Fatni Mufit; Nofi Yendri Sudiar Nofi Yendri Sudiar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2022)
Volcanic soil is a part of interest for physical, chemical, and morphology studies of soil derived from volcanic ash, which is known to be fertile and is one of the most productive soils in the world. They are also known to have a high environmental carrying capacity, as evidenced by the dense population in the area around the volcano. The soil contains many minerals, one of which is magnetic minerals. However, there is no document so far that records the value of the magnetic susceptibility of volcanic soil on the surface of Mount Singgalang. This study aims to determine the abundance of magnetic minerals based on their magnetic susceptibility values. To achieve this goal, the rock magnetism method is applied with the Bartington magnetic susceptibility meter type MS2B sensor instrument. Magnetic susceptibility values can be used as initial characteristics to understand past volcanic processes and explain environmental changes. This method is very effective, inexpensive, sensitive, fast, and non-destructive. The results showed that the value of the magnetic susceptibility of volcanic soils varied with a value range of 93.3 - 352.5 (x10-8 m3/kg). Based on this value, it is assumed that the magnetic mineral properties are antiferromagnetic. The average frequency dependent susceptibility (Xfd) (%) ranges from 0.831 - 2.090 %, indicating that the measured volcanic soil contains almost no superparamagnetic grains and is generally dominated by multi-domain grains.